Identification of Quality Open Green Space in Blang Padang Areas - Resky Rusnanda; Nasrullah Ridwan (LPPM Politeknik Aceh Selatan, 2019)
The city of Banda Aceh is the capital of Aceh where people work, from work to school. But the more the population increases, the less green open space in the Banda Aceh region and no longer fulfills its function as supporting the ecological, aesthetic, social, cultural and economic quality of the city. The purpose of this study is to find the composition of the proportion and distribution of green open space, especially in the downtown area of Banda Aceh appropriate to produce a concept penatan green open space in accordance with its function as a support for the ecological quality of the city which is also in accordance with the typology of Banda Aceh.